2006
DOI: 10.1002/ana.20784
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin causes regression of astrocytomas in tuberous sclerosis complex

Abstract: Oral rapamycin therapy can induce regression of astrocytomas associated with TSC and may offer an alternative to operative therapy of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
383
2
15

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 573 publications
(406 citation statements)
references
References 31 publications
6
383
2
15
Order By: Relevance
“…These effects suggest that rapamycin may have effects on neuronal function but that enhanced neuronal excitability is not a consequence of rapamycin treatment. The results of a recent pilot study on five patients with TSC treated with rapamycin which demonstrated a regression of astrocytomas supported this assumption (Franz et al, 2006). In view of planned larger human trials evaluating rapamycin to slow or prevent formation of tubers in TSC patients, it was important to confirm this "no effect" hypothesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These effects suggest that rapamycin may have effects on neuronal function but that enhanced neuronal excitability is not a consequence of rapamycin treatment. The results of a recent pilot study on five patients with TSC treated with rapamycin which demonstrated a regression of astrocytomas supported this assumption (Franz et al, 2006). In view of planned larger human trials evaluating rapamycin to slow or prevent formation of tubers in TSC patients, it was important to confirm this "no effect" hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…One group recently reported rapamycin-induced regression of astrocytomas in five patients with TSC. Four of these patients remained seizure-free during the treatment period; no information is given on seizure frequency of the fifth patient or on other neurological side effects (Franz et al, 2006). In the light of planned clinical trials for rapamycin in young patients, we investigated the effect of rapamycin on cell morphology, gene expression, and seizure-like firing patterns in cultured rat hippocampal neurons at postnatal time periods using morphometry, single cell mRNA amplification, and single unit recoding.…”
Section: Introductionmentioning
confidence: 99%
“…The first case report of rapamycin-therapy for TSCassociated tumors in patients has been published in 2006 (Franz et al, 2006). Four TSC-patients with SEGAs and one with a pilocytic astrocytoma were treated with oral rapamycin at standard immunosuppressive doses (serum levels 5-15 ng/ml) for 2.5-20 months.…”
Section: The Mtorc1 Inhibitors As Treatment For Tscmentioning
confidence: 99%
“…Only one ‘professional’ raised the prospect of syndrome‐specific medication, highlighting the treatment of brain tumours in tuberous sclerosis (Franz et al . 2006), a breakthrough that this respondent saw as likely to extend people's lives and dramatically improve their well‐being. That only one respondent drew attention to the advance in syndrome‐specific medication may reflect our small sample size but also it may signal the belief that neurodevelopmental conditions are essentially incurable.…”
Section: Stakeholder Views On the Utility Of Syndrome‐specific Knowledgementioning
confidence: 99%
“…Of possibly more immediate benefit is the development of pharmaceuticals that have the potential to shrink the tumours associated with tuberous sclerosis (Franz et al . 2006). With respect to studies of behavioural, as opposed to the physical phenotypes, research suggests that what appear to be ostensibly similar behaviours – self‐injury, temper tantrums and aggression – might have entirely different causes (Oliver et al .…”
Section: Introductionmentioning
confidence: 99%